The school in Bosnia and Herzegovina after the wars in the Balkans. Processes of conflict and peace in education - Luca Bravi (University of Bologna, 2023)
The Dayton Accords (1995) officially marked the end of wars in the Balkans, but the situation of political fragmentation and ethnic hatred resulting from the conflict continued to be present in the social context. In Bosnia and Herzegovina, school policy is a result of hatred that flared up in the years of conflict. Bosnia and Herzegovina was a multicultural territory before the war, in which Muslim, Serbian and Croatian communities coexisted peacefully. Since 1995, Bosnia represents a case of pacification accomplished through the international diplomacy, but which has materialized in a division of internal borders. Two schools under one roof is the title of a project that was conceived in the post-war period, in the Federation of Bosnia and Herzegovina. This model provides the separation of students on an ethnic and religious basis: different programs are adopted in the various classes, depending on the enclave to which they belong to; in this context of growing conflict expressed in educational policies, attempts to meet and dialogue are built by students and civil population.